High prevalence of complementary and alternative medicine use in patients with genetically proven mitochondrial disorders. Issue 3 (11th October 2014) - Franik, Sebastian; Huidekoper, Hidde H.; Visser, Gepke; de Vries, Maaike; de Boer, Lonneke; Hermans‐Peters, Marion; Rodenburg, Richard; Verhaak, Chris; Vlieger, Arine M.; Smeitink, Jan A. M.; Janssen, Mirian C. H.; Wortmann, Saskia B.
Abstract: Despite major advances in understanding the pathophysiology of mitochondrial diseases, clinical management of these conditions remains largely supportive, and no effective treatment is available. We therefore assumed that the burden of disease combined with the lack of adequate treatment leaves open a big market for complementary and alternative medicine use. The objective of this study was to evaluate the use and perceived effectiveness of complementary and alternative medicine in children and adults with genetically proven mitochondrial disease. The reported use was surprisingly high, with 88 % of children and 91 % of adults having used some kind of complementary and alternative medicine in the last 2 years. Also, the mean cost of these treatments was impressive, being €489/year for children and €359/year for adult patients. Over‐the‐counter remedies (e.g., food supplements, homeopathy) and self‐help techniques (e.g., Reiki, yoga) were the most frequently used complementary and alternative therapies in our cohort: 54 % of children and 60 % of adults reported the various complementary and alternative medicine therapies to be effective. Given the fact that currently no effective treatment exists, further research toward the different therapies is needed, as our study clearly demonstrates that such therapies are highly sought after by affected patients.